THE EFFECT OF SHARIA FINANCIAL LITERACY AND REPUTATION ON THE INTENTION TO USE SHARIA BANKS AMONG GENERATION Z IN YOGYAKARTA WITH RELIGIOSITY AS A MEDIATION VARIABLE - Affra Riska Amalia Misladiah; Sutrisno Amalia Sutrisno (Universitas KH. Abdul Chalim Mojokerto, 2026)
The low level of sharia banking inclusion among Generation Z is an important issue even though the majority of Indonesia's population is Muslim. This study aims to analyze the effect of sharia financial literacy and sharia bank reputation on the intention to use sharia banks with religiosity as a mediating variable among Generation Z in Yogyakarta. The study uses a quantitative approach with purposive sampling and is analyzed using SEM-PLS. The results show that Islamic financial literacy, Islamic bank reputation, and religiosity have a positive and significant effect on the intention to use Islamic banks. Religiosity partially mediates the effect of literacy and reputation on intention. The limitations of this study lie in its geographical scope and the use of self-reported data. These findings emphasize the importance of improving literacy and strengthening reputation based on sharia compliance to increase the interest of Generation Z.